Expression of PD‐L1 in tumor‐associated nerves correlates with reduced CD8+ tumor‐associated lymphocytes and poor prognosis in prostate cancer. Issue 12 (16th January 2019) - Mo, Ru‐Jun; Han, Zhao‐Dong; Liang, Ying‐Ke; Ye, Jian‐Heng; Wu, Shu‐Lin; Lin, Sharron X.; Zhang, Yan‐Qiong; Song, Sheng‐Da; Jiang, Fu‐Neng; Zhong, Wei‐De; Wu, Chin‐Lee
Abstract : To investigate immune profile consisting of stromal PD‐L1 expression, inhibitory or non‐T‐cell inflamed tumor microenvironment that may predict response to anti‐PD‐L1/PD‐1 immunotherapy in prostate cancer, we validated the specificity of a PD‐L1 monoclonal antibody (E1L3N) and identified PD‐L1 specific expression in prostatic stromal nerve cells. PD‐L1 expression was analyzed in 73 primary prostate cancers and 7 castration‐resistant prostate cancers (CRPC) by immunohistochemistry (IHC) and resulting data from primary prostate cancers were correlated with tumor‐associated lymphocytes (TALs), clinicopathological characteristics and clinical outcome. PD‐L1 was expressed in the tumor cells in only one primary prostate cancer case and none of the CRPC. However, PD‐L1 was frequently observed in the nerve branches in the tumor‐associated stroma (69 of 73 cases, 94.5%), supported by colocalization with axonal marker PGP9.5. FoxP3‐, CD3‐ and CD8‐positive T lymphocytes were observed in 74.6% (47/63), 98.4% (62/63) and 100% (61/61) of the cases, respectively. The density of PD‐L1 + tumor‐associated nerves (TANs) was inversely correlated with that of CD8 + TALs. Higher density of PD‐L1 + TANs was significantly associated with biochemical recurrence (BCR) in Kaplan–Meier survival analysis ( p = 0.016). In both univariate and multivariate Cox analysis, the density of PD‐L1 + TANs was independently prognostic of BCR. In conclusion, PD‐L1 expression is rare in prostate tumor cells but prevalent in TANs and negatively correlated with CD8 + TALs. Neuro‐immunological interaction may be a contribution to immune‐suppressive microenvironment. Combinatorial treatment regimen designs to neural PD‐L1 and TALs should be warranted in future clinical application of anti‐PD‐L1/PD‐1 immunotherapy in prostate cancer. Abstract : What's new? Immunotherapies targeting programmed cell death protein 1 (PD‐1) and its ligand PD‐L1 display durable clinical benefit across various cancer types. However, an immunosuppressive tumor microenvironment has been suggested to underlie the resistance to anti‐PD‐L1/PD‐1 monotherapy in prostate cancer patients. This study investigates stromal PD‐L1 and its relationship with tumor‐associated lymphocytes (TALs) in prostate cancer. The findings indicate that PD‐L1 is expressed in tumor‐associated nerves (TANs) and that high density of PD‐L1 + TANs correlates with reduced CD8 + TALs and predicts poor prognosis of prostate cancer. Combinatorial treatment targeting neural PD‐L1 and TALs should be warranted in anti‐PD‐L1/PD‐1 immunotherapies for prostate cancer.